2022
DOI: 10.1021/acsanm.2c02538
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Two-Dimensional Monolayer PdSe2 for Selective Sensing of Nitrogen-Containing Gases

Abstract: Monolayer palladium diselenide (PdSe 2 ) has attracted increasing attention due to its outstanding physicochemical properties and puckered pentagonal layered structure. In this study, the adsorption of nitrogen-containing gases on the surface of monolayer PdSe 2 has been investigated by first-principles calculations to fully explore its gas-sensing capability. It is found that NH 3 and N 2 O show physisorption, while NO 2 and NO prefer chemisorption, indicating excellent selectivity of monolayer PdSe 2 . Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…As industrialization has grown in recent years, the amount of polluting gases in the air have increased, which are particularly harmful to the environment and public health. Therefore, it makes sense to remove and capture these toxic gases from the environment using effective methods. In order to identify such air pollutants, highly sensitive sensors with high selectivity, fast response, and recovery of sorbents to toxic substances are urgently needed. Due to their high surface-to-volume ratio, two-dimensional (2D) nanomaterials have gained significant interest from researchers in recent years as efficient gas sensors. The discovery of graphene led to studies on the sensing potential of 2D nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…As industrialization has grown in recent years, the amount of polluting gases in the air have increased, which are particularly harmful to the environment and public health. Therefore, it makes sense to remove and capture these toxic gases from the environment using effective methods. In order to identify such air pollutants, highly sensitive sensors with high selectivity, fast response, and recovery of sorbents to toxic substances are urgently needed. Due to their high surface-to-volume ratio, two-dimensional (2D) nanomaterials have gained significant interest from researchers in recent years as efficient gas sensors. The discovery of graphene led to studies on the sensing potential of 2D nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials have been widely investigated due to their large surface-to-volume ratio, high surface activities, and distinct thickness-dependent physical and chemical properties. So far, some intrinsic 2D materials such as graphene, transition metal dichalcogenides (TMDCs), boron–phosphorus, phosphorene, and silicene have been extensively studied as gas-sensing materials due to their excellent selectivity and sensitivity. According to the different charge transfer mechanisms, the gas molecules adsorbing on the surface of the 2D materials can act as electron donors or acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…20−24 Recent experiments and calculations have been conducted on monolayer and few-layer PdSe 2 gas sensors, and it has been found that PdSe 2 is a promising sensing material exhibiting sensitive responses toward nitrogen dioxide (NO 2 ) gas and good reusability at room temperature. 5,25,26 Unfortunately, there are no studies to explore whether the monolayer PdS 2 is suitable for gas sensors up to now.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] NMDCs not only possess anisotropic structures, low-energy differences between different crystalline phases and controllable phase transitions compared to conventional TMDCs, but also exhibit promising application potential in field-effect transistors, photodetectors, sensors, photocatalysts and photovoltaic cells. [31][32][33][34][35][36][37] Particularly, the bulk phases of diselenides or disulphides of palladium (PdX 2 , X = S, and Se) crystallize in a peculiar puckered pentagonal structure (2O type), instead of the common 1T, 2H or 3R structure of TMDCs. 38 Although equilateral pentagons with good symmetry are regarded as topological or geometrical defects and cannot be used as planar structural motifs, low-symmetry type-II pentagons can spread over the entire plane and lead to Cairo tessellation.…”
Section: Introductionmentioning
confidence: 99%
“…26–30 NMDCs not only possess anisotropic structures, low-energy differences between different crystalline phases and controllable phase transitions compared to conventional TMDCs, but also exhibit promising application potential in field-effect transistors, photodetectors, sensors, photocatalysts and photovoltaic cells. 31–37…”
Section: Introductionmentioning
confidence: 99%